How Translation Techniques Affect the Quality of Metaphor Translation in Kesatria, Putri, dan Bintang Jatuh? - Salsadila Sindya Dewantari; Mangatur Rudolf Nababan; Agus Hari Wibowo (Journal of Social Research, 2024)
Translation is a crucial aspect of cross-cultural communication, which involves not only the conversion of words from one language to another but also the preservation of cultural nuances and literary elements, which are pivotal to maintaining the literary and communicative integrity of a text across languages. Translation, as a critical aspect of cultural communication, is critical for maintaining the beauty and intended meaning of the original author. In this study, a novel titled Kesatria, Putri, dan Bintang Jatuh, was translated from Bahasa Indonesia into English using six different translation techniques. The findings show that modulation, paraphrase, and established equivalent do not impact accuracy, acceptability, and readability, as they effectively preserved the original meaning. These findings highlight the importance of flexibility and creativity in translation, as translators must navigate cultural and linguistic differences while striving to preserve the original intent and emotional resonance of the source material. This study aims to contribute to the ongoing discourse on effective literary translation practices and enhance the appreciation of metaphorical language across cultures.